Engineered, harnessed, and hijacked: synthetic uses for cytoskeletal systems - Goodman, Brian S. (2012)
Synthetic biology re-imagines existing biological systems by designing and constructing new biological parts, devices, and systems. In the arena of cytoskeletal-based transport, synthetic approaches are currently used in two broad ways. First, molecular motors are harnessed for non-physiological functions in cells. Second, transport systems are engineered in vitro to determine the biophysical rules that govern motility. These rules are then applied to synthetic nanotechnological systems. We review recent advances in both of these areas and conclude by discussing future directions in engineering the cytoskeleton and its motors for transport.